Live Lectures: The Significance of Presence in Building Disciplinary Knowledge - Hood, Susan (Onomázein, 2017)
Radical changes in modes of pedagogy are currently being implemented in higher edu-cation internationally. Most significantly there is a rapid movement away from face-to-face, or ‘live’ teaching in lecture mode toward online-only resources, or to ‘flipped classrooms’. The arguments mounted in support of such changes vary from economic imperatives to life-style preferences to pedagogic benefits. However, the research base in relation to the latter remains disturbingly thin. There is an overreliance on small-scale opinion survey data in the immediate context of changed practice and very little exploration of the nature of pedagogic practice in online modes or in the face-to-face lecturing they replace. Significantly lacking are attempts to tease apart the impact of technologies, modes of communication, pedagogic models and disciplinary knowledge structures in the building of knowledge. This study makes an initial contribution to this substantial project in an exploratory analysis of the dynam-ic unfolding of meaning in the spoken discourse of a face-to-face lecture in health science. The approach is trans-disciplinary, drawing both on systemic functional linguistics (SFL) and Legitimation Code Theory (LCT). Findings reveal ways in which meanings shift between the here-and-now of the shared sensible material space and elevated reflective perspectives on the field, and in doing so support the apprenticeship of students into the specialized, uncom-mon-sense knowledge of their field.